Characterization and synthesis of three-armed copolymers of phenoxycarbonylmethyl methacrylate and ethyl methacrylate via atom transfer radical polymerization - Demirelli, K; Kurt, A; Coskun, MF; Coskun, M (Taylor & Francis Inc, 2006)
1,3,5-(2'-Bromo-2'-methylpropionato)benzene was used as a three-functional initiator in the synthesis of three-armed star polymer of phenoxycarbonylmethyl methacrylate (PCMMA) and its copolymers with ethylmethacrylate (EMA) via the atom transfer radical polymerization (ATRP) with a Cu(I)Br/2,2'-bipyridine catalitic system at 90 degrees C. The homo- and copolymers were characterized by FT-IR, H-1 and C-13 NMR techniques. The compositions of the copolymers were calculated from H-1-NMR spectra. The diblock copolymer of poly(PCMMA-b-EMA) synthesized using poly(PCMMA) macroinitiator and Cu(I)Br/bpy catalitic system showed an inefficient polymerization of ethylmethacrylate with low molecular weight and higher polydispersity. The molecular weight and molecular weight distribution were obtained by Gel Permeation Chromatography (GPC). For this copolymerization system, their monomer reactivity ratios were obtained by using both Kelen-Tudos and Fineman-Ross equations. The thermal behavior of three-armed poly(PCMMA) and its copolymers were studied by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Three-armed poly(PCMMA) heated to 270 degrees C was characterized by GPC.
Keywords: ATRP; star polymer; synthesis; monomer reactivity ratio; copolymerization of PCMMA and EMA by ATRP